2019
DOI: 10.1519/jsc.0000000000002438
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Asymmetries in Change of Direction Speed Performance: Application of Change of Direction Deficit

Abstract: The aims of this study were to quantify asymmetries in change of direction (COD) performance via completion time and COD deficit, and determine its influence on asymmetry profiling of COD ability. A secondary aim was to evaluate the relationship between linear speed, 505 time and COD deficit. Forty-three youth netball athletes (age: 15.4 ± 1.1 years, height: 1.71 ± 0.06 m, mass: 63.3 ± 6.6 kg) performed the 505 for both left and right limbs and a 10 m sprint test. Asymmetries in 505 completion time and COD def… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
144
2
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 84 publications
(165 citation statements)
references
References 27 publications
17
144
2
2
Order By: Relevance
“…COD test showed a lower magnitude of asymmetry (COD5: 4.60% ± 2.51% and COD10: 3.02% ± 1.74%) in comparison to the jump and iso-inertial power tests, which is in agreement with previous research (Fort-Vanmeerhaeghe et al, 2015;Dos'Santos et al, 2018;Madruga-Parera et al, 2019). The COD tests' inability to detect asymmetries could be due to two reasons: first, there is a strong linear speed component during COD, mainly in COD10 (Madruga-Parera et al, 2019), and second, sprint times are far more replicable than power outputs during jump (Bishop et al, 2019a) or iso-inertial tests.…”
Section: Discussionsupporting
confidence: 92%
“…COD test showed a lower magnitude of asymmetry (COD5: 4.60% ± 2.51% and COD10: 3.02% ± 1.74%) in comparison to the jump and iso-inertial power tests, which is in agreement with previous research (Fort-Vanmeerhaeghe et al, 2015;Dos'Santos et al, 2018;Madruga-Parera et al, 2019). The COD tests' inability to detect asymmetries could be due to two reasons: first, there is a strong linear speed component during COD, mainly in COD10 (Madruga-Parera et al, 2019), and second, sprint times are far more replicable than power outputs during jump (Bishop et al, 2019a) or iso-inertial tests.…”
Section: Discussionsupporting
confidence: 92%
“…The present findings are in line with the study of Dos'Santos et al (2019b), which reported asymmetries of COD d (in the 505 COD test) on average greater than 10% in youth netball players. Moreover, the authors found that asymmetries of COD d were approximately fivefold greater than asymmetries of total time (−11.9% vs. −2.3%, respectively).…”
Section: Discussionsupporting
confidence: 93%
“…This calculation was also applied by using the same formula replacing the values with COD d (Dos'Santos et al, 2019b). Moreover, as previously proposed by Dos'Santos et al (2019b) and Trecroci et al (2020) an asymmetry threshold (AT%) was also computed for each group by the following formula:…”
Section: Asymmetric Index Calculationmentioning
confidence: 99%
See 1 more Smart Citation
“…These contradictions could be solved by introducing the concept of deficit in COD, where COD action is isolated from linear action within the tests [ 53 ]. While several studies [ 54 , 55 ] have shown the relationship of CODs to the deficit itself, no considerations have been made with linear velocity. Although some authors [ 56 ] still suggest linear velocity to be a determining factor for COD performance, high COD approaching velocities may increase the loads which the knee receives in valgus.…”
Section: Discussionmentioning
confidence: 99%